2022
DOI: 10.3389/fcvm.2022.916156
|View full text |Cite
|
Sign up to set email alerts
|

Early antithrombotic post-discharge therapy using prophylactic DOAC or dipyridamole improves long-term survival and cardiovascular outcomes in hospitalized COVID-19 survivors

Abstract: IntroductionCardiovascular events are common in COVID-19. While the use of anticoagulation during hospitalization has been established in current guidelines, recommendations regarding antithrombotic therapy in the post-discharge period are conflicting.MethodsTo investigate this issue, we conducted a retrospective follow-up (393 ± 87 days) of 1,746 consecutive patients, hospitalized with and surviving COVID-19 pneumonia at a single tertiary medical center between April and December 2020. Survivors received eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
4
0
4
Order By: Relevance
“…Tromboprofilaxia com DOAC mostrou-se eficaz na redução de AVC e TEP após a alta hospitalar de 1002 pacientes internados pela COVID-19. A ocorrência de TEP e AVC foi 5,3 vezes maior no grupo controle composto por 440 doentes (sem tromboprofilaxia) após a alta, evidenciando vantagem do uso de DOACs para este fim no período de aproximadamente 393 dias de observação do estudo, DOACs reduziram TEP em 42% (p = 0,012) e AVC em 23% (p = 0,028) (MOTLOCH LJ, et al, 2022). Um estudo prospectivo avaliou dupla terapia com DOAC (dabigatrana e endoxabana) em 25 pacientes e outra dupla terapia com apixabana e rivaroxabana em 12 doentes, em um contexto de 39 pacientes os quais estavam internados com COVID-19 e com ocorrência de TEP.…”
Section: Resultsunclassified
“…Tromboprofilaxia com DOAC mostrou-se eficaz na redução de AVC e TEP após a alta hospitalar de 1002 pacientes internados pela COVID-19. A ocorrência de TEP e AVC foi 5,3 vezes maior no grupo controle composto por 440 doentes (sem tromboprofilaxia) após a alta, evidenciando vantagem do uso de DOACs para este fim no período de aproximadamente 393 dias de observação do estudo, DOACs reduziram TEP em 42% (p = 0,012) e AVC em 23% (p = 0,028) (MOTLOCH LJ, et al, 2022). Um estudo prospectivo avaliou dupla terapia com DOAC (dabigatrana e endoxabana) em 25 pacientes e outra dupla terapia com apixabana e rivaroxabana em 12 doentes, em um contexto de 39 pacientes os quais estavam internados com COVID-19 e com ocorrência de TEP.…”
Section: Resultsunclassified
“…Likewise, most of the included studies in this systematic review agreed with post-discharge VTE thromboprophylaxis if the patient's risk assessment indicated a high-risk situation for VTE. In between, three good-quality cohort studies reported a significant association between post-discharge VTE risk reduction and extended thromboprophylaxis [ 22 , 30 , 36 ]. As in the study by Li et al, this risk reduction was stated to be 82%; although, in the Courtney et al study, the chance of bleeding increased significantly with post-discharge AC [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three high-quality studies, including the MICHELLE trial, recommended rivaroxaban 10mg daily for 30–35 days. Alternatively, apixaban 2.5mg BID and dabigatran 110mg BID can be used as the choices of DOACs [ 11 , 25 , 36 ]. Also, ISTH, the anticoagulation forum, the VAS, and the health system anticoagulation task force guidelines favored rivaroxaban 10mg daily for 30–42 days [ 35 , 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of cardiac injury biomarkers such as N-terminal pro-B-type natriuretic peptide (NT-proBNP), cTn, or D-dimer were associated with a worse prognosis in the course of SARS-CoV2 infection [21]. There are findings of elevated creatine kinase MB fraction (CK-MB) as well as IL-6 levels in COVID-19 patients with acute myocardial injury [22]. Similarly, elevated fibrinogen and D-dimer have been shown predictors of poor prognostic outcome in hospitalized patients with COVID-19 [23].…”
Section: Clinical Cardiovascular Manifestations Of Covid-19mentioning
confidence: 99%